In vivo interspecies dissemination of IncM2-type blaNDM-1 carrying plasmid - Mor N. Lurie-Weinberger; Darya Bychenko-Banyas; Meirav Mor; Sivan Laviad-Shitrit; Ella Kaplan; Nadya Rakovitsky; Alona Keren-Paz; Chaim Ben-Zvi; Yehuda Carmeli (Microbiology Spectrum)
ABSTRACT The gastrointestinal tract is a unique ecological niche with a high abundance of various Enterobacterales in close proximity. This allows the exchange of mobile genetic elements that carry resistance determinants. In the hospital setting, resistant organisms are prevalent and selective antibiotic pressure is high, providing a supportive platform for interspecies dissemination of resistance. Seven New Delhi metallo-beta-lactamase(NDM) positive and one NDM-negative bacteria were sent for WGS followed by bioinformatics analysis. Here, we describe three separate cases of patients simultaneously colonized by two NDM producing-species (Escherichia coli and Klebsiella pneumoniae), in which we documented interspecies dissemination of the blaNDM-1 by an 87,450 bp IncM2 type multi-drug resistance plasmid (here named pNCICAN_NDM-01_21-il). This plasmid was found to be highly conjugative. Our results underline the risk of interspecies horizontal plasmid dissemination. Such events may cause the emergence of high-risk clones, as well as lead to under-recognized multi-species outbreaks.IMPORTANCEConjugative, carbapenemase-carrying multidrug-resistant plasmids that can move between species of clinically relevant Enterobacterales pose a great risk to patients’ health, especially when they spread inside a medical institution. Yet, most institutions monitor bacteria according to species and are at risk of missing plasmid-driven outbreaks. Thus, this work indicates that plasmid surveillance is an important tool for infection control.